The impact of energy systems demands on pressure limited CO2 storage in the Bunter Sandstone of the UK Southern North Sea. (October 2017) - Agada, Simeon; Jackson, Samuel; Kolster, Clea; Dowell, Niall Mac; Williams, Gareth; Vosper, Hayley; Williams, John; Krevor, Samuel
Highlights: National techno-economic pathways to reduce carbon emissions are required for the United Kingdom to meet its decarbonisation obligations as mandated by the Paris Agreement. Analysis using energy systems models indicate that carbon capture and storage is a key technology for the UK to achieve its mitigation targets at lowest cost. We generate a range of numerical simulations of CO2 injection into the Bunter Sandstone to evaluate sensitivities of a given reservoir system to future development pathways. The numerical simulations are matched with analytical models of local and regional pressurisation. Discrepancies in the match are mostly due to the interaction of signals from multiple injection sites and heterogeneous permeability in the numerical simulations. Abstract: National techno-economic pathways to reduce carbon emissions are required for the United Kingdom to meet its decarbonisation obligations as mandated by the Paris Agreement. Analysis using energy systems models indicate that carbon capture and storage is a key technology for the UK to achieve its mitigation targets at lowest cost. There is potential to significantly improve upon the representation of the CO2 storage systems used in these models, but sensitivities of a given reservoir system to future development pathways must be evaluated. To investigate this we generate a range of numerical simulations of CO2 injection into the Bunter Sandstone of the UK Southern North Sea, considered to be one of the most important regional aquifers for CO2 storage. The scenarios investigate the sensitivity of CO2 storage to characteristics of regional development including number of injection sites and target rates of CO2 injection. This enables an evaluation of the impact of a range of deployment possibilities reflecting the range of scenarios that may be explored in an energy system analysis. The results show that limitations in achieving target injection rates are encountered at rates greater than 2 MtCO2 /year-site due to local pressure buildup. The areal location of injection sites has minimal impact on the results because the Bunter Sandstone model has good regional connectivity. Rather, the depth of the site is the most important factor controlling limits on CO2 injection due to the relationship between the limiting pressure and the lithostatic pressure gradient. The potential for model simplification is explored by comparison of reservoir simulation with analytical models of average reservoir pressure and near-site pressure. The numerical simulations match average pressure buildup estimated with the "closed-box" analytical model of Zhou et al. (2008) over a 50 year injection period. The pressure buildup at individual sites is estimated using the Mathias et al. (2011) formulation and compared to the simulation response. Discrepancies in the match are mostly due to the interaction of signals from multiple injection sites and heterogeneous permeability in the numerical simulations. These issues should be the focus of further development of simplified models for CO2 storage in an energy systems analysis framework.